Ametropías y su relación con las habilidades de lectoescritura en niños del Rcto. Rosa María – Babahoyo - octubre 2024 - abril 2025. - Márquez Parrales, Javier Francisco (2025)
Ametropias and their relationship with reading and writing skills in children from the Rcto. Rosa María - Babahoyo. October 2024 - April 2025. Ametropias are an anomaly in the refractive media of the eye. The objective was to analyze the relationship of ametropias with the development of reading and writing skills in children aged 8 to 10 years at the Rcto. Rosa María. The methodology was quantitative, descriptive, cross-sectional field, deductive and analysis methods were applied; the population was 75 children, using the exclusion and inclusion criteria, a sample of 45 children was determined, observation was used as a technique, the clinical history and the T.A.L.E test were used as an instrument to quantify reading and writing skills. Results: The highest age range was in children aged 9 years with 51%, the female gender predominated, in the symptomatology 42% presented double vision and 24% headache, the ametropias identified were myopia with 38%, myopic astigmatism 44% and pure astigmatism 18%, the visual acuity that the children presented was 20/40 and 20/60, in the T.A.L.E test the children obtained a high score in the group of 9 years, who went from level 3 and 4 to level 5 in reading and writing with optometric correction. It is concluded that the different ametropias detected in children from 8 to 10 years significantly affect the development of their reading and writing skills, demonstrating that children already optically corrected presented a better development in their skills.